TINJAUAN YURIDIS KOMPETENSI RELATIF PENGADILAN NIAGA TERHADAP PUTUSAN PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG PT. PEMBANGUNAN PERUMAHAN BERDASARKAN UNDANG-UNDANG NOMOR 37 TAHUN 2004 TENTANG KEPAILITAN DAN PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG - Al Fani, Muhammad; Fauziah, Faridatul; Efriyanto, Efriyanto (LPPM Universitas Bina Bangsa, 2025)
PT Pembangunan Perumahan is a state-owned enterprise (BUMN) structured as a limited liability company with shares divided between government ownership and public ownership in the form of common shares. PT Pembangunan Perumahan has a legal relationship with CV Surya Mas through an agreement regarding project work, which includes provisions on dispute resolution specifying a mutually agreed-upon jurisdictional domicile that is binding on both parties. However, a conflict arose when the Commercial Court, which actually lacks authority in this matter, granted a request for a Suspension of Debt Payment Obligations (PKPU) solely due to the jurisdictional choice specified in the agreement. This study identifies questions such as: what is the strength of a cooperation agreement that includes the selection of legal domicile in dispute resolution concerning a case of debt payment suspension at the Commercial Court? Furthermore, what were the considerations of the judge in Decision Number 9/Pdt.Sus-PKPU/2023/PN Niaga Mks, regarding the legal domicile of PT Pembangunan Perumahan according to applicable law? This research utilizes legal certainty theory and employs a normative juridical method. The acceptance of the PKPU petition for PT Pembangunan Perumahan does not comply with Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations, Article 3, Paragraphs (1) and (5), which should consider the debtor's domicile. Law Number 37 of 2004 on Bankruptcy and PKPU is specialized law; thus, it does not allow for a choice of law in bankruptcy and PKPU petitions. In PKPU cases, the Commercial Court is not bound by the legal jurisdiction and domicile chosen in the agreement between the parties.